Repositioning developing countries in WTO - Lal Das, Bhagirath (1998)
Discusses a twin trend viz. the ignoring of the basic interests of the developing countries by the GATT/WTO system, and the extraction of significant concessions from them. Identifies reasons for these trends and makes some suggestions for improving the situation.